Facial Swelling After Dental Work Done: A Case of Ludwig's Angina. (January 2023) - Gonzalez, Juan Manuel; McGhee, Stephen; Nadeau, Catherine; Ortega, Johis
Abstract : Ludwig's angina is a fast-spreading cellulitis located on the floor of the oropharynx and neck (Tami, Othman, Sudhakar, & McKinnon, 2020 ). Patients may present with a wide range of symptoms depending on the severity of the condition (Reynolds & Chow, 2007 ). Emergency nurse practitioners need to promptly identify, diagnose, and treat patients with this problem, with close attention to the patient's airway. A compromised airway is the leading cause of mortality from this condition (McDonnough et al., 2019 ). The diagnosis is generally made with a comprehensive history and physical examination, laboratory values, and imaging studies such as computer tomography (Bridwell, Gottlieb, Koyfman, & Long, 2021 ). Management includes admission to the hospital, broad-spectrum antibiotics, and specialist surgical consultation (Bridwell et al., 2021 ).